Development of Block Cipher Cryptography Based on Denok Deblong Dance Pattern - Yuana Sambadha sambadha (JUTEI (Jurnal Terapan Teknologi Informasi), 2019)
The popularity of cybercrime caused unsafe information. Infrastructure IT made an effort to take in hand the problem, i.e. manipulating information. Cryptography existed as knowledge to protect information. To improve the security level, cryptography needs to be developed. Block Cipher Cryptography based on Dance Denok Deblong is designed to create a new cryptography. This cryptography is designed by using 4 process and 20 rounds. In fourth procesis transformed with S-BOX to get a more random ciphertext. Testing is also done using Avalanche Effect and Correlation value where the character change reaches 49,844%, so it can be used as an alternative in securing data